Mobile networks and management Second International ICST Conference, MONAMI 2010, Santander, Spain, September 22-24, 2010, Revised Selected Papers - Pentikousis, Kostas; Agüero, Ramón; García-Arranz, Marta; Papavassiliou, Symeon (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on Mobile Networks and Management, MONAMI 2010, held in Santander, Spain in September 2010. The 29 revised full papers presented were carefully reviewed and selected for inclusion in the proceedings. The papers are organized in topical sections on routing and virtualization, autonomic networking, mobility management, multiaccess selection, wireless network management, wireless networks, and future research directions.